2015
DOI: 10.1007/s11356-015-4833-8
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and degradation mechanism of an anaerobic bacterial community treating phenolic wastewater with sulfate as an electron acceptor

Abstract: Petrochemical wastewater often contains high concentrations of phenol and sulfate that must be properly treated to meet discharge standards. This study acclimated anaerobic-activated sludge to treat saline phenolic wastewater with sulfate reduction and clarified the diversity and degradation mechanism of the microbial community. The active sludge in an upflow anaerobic sludge blanket (UASB) reactor could remove 90 % of phenol and maintain the effluent concentration of SO4 (2-) below 400 mg/L. Cloning and seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 33 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Though Ottowia has been isolated from activated sludge treating CWW wastewater (Felfoldi et al 2011;Cao et al 2014;Geng et al 2014), its presence at such a high abundance in anaerobic sludge was not reported previously. The presence of Ottowia together with Advenella Ghosh et al 2011), Corynebacterium (Dalal et al 2012;Guo et al 2015), and Sphingobium (Kertesz and Kawasaki 2010) might be associated with the removal of phenols, NHCs as well as PAHs under the anaerobic conditions (Table S8). Soehngenia, the second most abundant anaerobic bacterium in this study, was previously reported to degrade benzaldehyde (Parshina et al 2003), an intermediate in anaerobic phenol degradation (Sharma and Philip 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Though Ottowia has been isolated from activated sludge treating CWW wastewater (Felfoldi et al 2011;Cao et al 2014;Geng et al 2014), its presence at such a high abundance in anaerobic sludge was not reported previously. The presence of Ottowia together with Advenella Ghosh et al 2011), Corynebacterium (Dalal et al 2012;Guo et al 2015), and Sphingobium (Kertesz and Kawasaki 2010) might be associated with the removal of phenols, NHCs as well as PAHs under the anaerobic conditions (Table S8). Soehngenia, the second most abundant anaerobic bacterium in this study, was previously reported to degrade benzaldehyde (Parshina et al 2003), an intermediate in anaerobic phenol degradation (Sharma and Philip 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Syngas accounted for over 90% of the total e-mol for the first 40 days of the fermentation. Although no significant correlation was identified between Clostridium sensu stricto 12 and aromatics removal in this work, prior research indicated that Clostridium sensu stricto participated in the anaerobic digestion of aromatics-rich wastewaters [73][74][75][76]. Examples include also the enrichment of Clostridium sensu stricto (up to 17.5%) during the degradation of tars from rice husk gasification, where biochar facilitated syntrophic relations with Methanosaeta [26].…”
Section: Reactor Microbiomes and Performances Of The Mesophilic And T...mentioning
confidence: 54%
“…Anaerobic treatment of phenol-containing wastewater is mostly performed in UASB (up-flow anaerobic sludge blanket) reactors [ 41 ]. Guo et al achieved up to 90% phenol removal using a UASB reactor based on sulfate reduction [ 42 ]. Sequencing 16s DNA showed that Clostridium spp.…”
Section: Rss-related Bioprocesses For the Treatment Of Environmental ...mentioning
confidence: 99%